Automated library serials (Ess Ess Pubications, 2001)
Contents of material: 1/ Introduction. 2/ National database. 3/ Serials cataloguing. 4/ Serials preservation. 5/ Developmenttal issues. 6/ Vendor selection. 7/ Nontranditional library employment. 8/ CD-ROM technologies. 9/ Jounal availability.